Escape from Furnace: Execution - Book 5 - Smith, Alexander Gordon 1979- (New York : Farrar, Straus, Giroux, 2012)
Alex Sawyer has escaped his underground nightmare to discover that the whole world has become a horrible prison run by his nemesis, Alfred Furnace, and only Alex can stop him, even if that makes him the executioner.
Keywords: Prisons -- Juvenile fiction; Fugitives from justice -- Juvenile fiction; Science fiction; Horror tales; Prisons -- Fiction; Fugitives from justice -- Fiction; Science fiction; Horror stories; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Boys & Men; JUVENILE FICTION / Law & Crime; JUVENILE FICTION / Monsters